Estabelecimento de espécies florestais nativas via semeadura direta no rio Piauitinga - SE - Jesus, Janisson Batista de (2015)
The way and the intensity of the exploration of natural resources throughout the time in Brazil, resulted, as consequence in a large number of areas with problems of environmental degradation mainly associated water resources. Like this became necessary the recovery through of techniques, direct sowing which point out by reduction of costs in the implantation and has been used increasingly. This work was accomplished with the objective to asses the emergency survival and establishment of forest species natives in seeds of Libidibia ferrea var. leiostachya (Benth.) L.P.Queiroz., Cassia grandis L.F., Cecropia pachystachya Trec., Enterolobium contortisiliquum (Vell.) Morong e Guazuma ulmifolia Lam., in riparian areas in the river Piauitinga, municipality of Lagarto-se. Analysis of physiological quality, morphometry and moisture content of seeds were previously evaluated in laboratory. The experiment at field was deployed in design randomized blocks (RBD) with four replications in factorial scheme, testing five species with and without treatment for overcoming of dormancy, being these previously treated in laboratory. The direct sowing was distributed in ten lines each one composing ten pits (30x30x30cm) in spacing 2,0m x 1,0m totaling 100 for block, being the density of sowing for species certain by previous tests in laboratory. It was analyzed the percentage of emergency, survival of the seeds, Relative Growth Rate (RGR) for the height and base diameter of the plants emerged in each treatment until the 180 days after sowing. The specie Cecropia pachystachya didn´t present anyone value of emergency this way with more parameters valued, they were canceled. The dormancy seeds Enterolobium contorsiliquum pointed out with the best index of emergence (74%) while for non dormancy Cassia grandis obtained the higher values (69,25%). About the survival for the seeds without treatment of overcoming of dormancy Libidibia ferrea var. leiostachya had 74,14 % while for the seeds with treatment Cassia grandis presented 61,01%. For the plants established emerged of the dormancy seeds at 180 days it was observed that Enterolobium contortisiliquum presented 95 % of survival. Already for without dormancy Cassia grandis showed the best percentage (82,5%). Abouth the growth of the plants in the height Enterolobium contortisiliquum obtained the bigger values for the treatments with (19,44cm) and without (12,06cm) at 180 days. Besides the same species presented the bigger values for base diameter with (3,1mm) and without (2,4mm) in the end of the period of study. There was variation as for comparison of the treatment for each specie however statistically didn´t check difference between averages for the parameters analyzed. The direct sowing showed to be a technique viable for the area of study only for the species L. ferrea var. leiostachya, E. contortisiliquum and Cassia grandis using seeds with and without dormancy, once that Cecropia pachystachya didn´t have index